2021
DOI: 10.1007/s10489-021-02311-8
|View full text |Cite
|
Sign up to set email alerts
|

Cure models to estimate time until hospitalization due to COVID-19

Abstract: A short introduction to survival analysis and censored data is included in this paper. A thorough literature review in the field of cure models has been done. An overview on the most important and recent approaches on parametric, semiparametric and nonparametric mixture cure models is also included. The main nonparametric and semiparametric approaches were applied to a real time dataset of COVID-19 patients from the first weeks of the epidemic in Galicia (NW Spain). The aim is to model the elapsed time from di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…From the applications of the model based on the DB distribution in real data, we observed that the posterior mean for β is not very sensitive to the choice of prior distributions for the parameter β. From the results obtained in this study, we can conclude that the proposed methodology can be very useful for researchers working with discrete medical life data in the presence of a cure fraction, a common situation in both medical and engineering applications [23,32,42,44].…”
Section: Discussionmentioning
confidence: 77%
“…From the applications of the model based on the DB distribution in real data, we observed that the posterior mean for β is not very sensitive to the choice of prior distributions for the parameter β. From the results obtained in this study, we can conclude that the proposed methodology can be very useful for researchers working with discrete medical life data in the presence of a cure fraction, a common situation in both medical and engineering applications [23,32,42,44].…”
Section: Discussionmentioning
confidence: 77%
“…We model this state as a cure model [ 38 ]. Cure models are a special type of survival analysis model wherein it is assumed that there is a proportion of subjects who will never experience the event of interest and thus the survival curve will eventually reach a plateau [ 39 ]. In our case, we consider that the cured patients are those who will not be admitted to hospital.…”
Section: Methodsmentioning
confidence: 99%
“…To compute the initial values of model parameters to start the NCG algorithm, we first calculated the non-parametric estimates of the cured proportions for nodule categories 1 and 4 (obtained by taking the Kaplan-Meier estimate of the survival function at the largest observed lifetime). Then, we equated these to p 0 (x) with x = 1 and 4, as in (7), for different values of 𝛼 in the interval [0, 1]. By solving the two equations for different values of 𝛼, we obtained a set of values of the regression parameters 𝛽 0 and 𝛽 1 .…”
Section: Real Data Applicationmentioning
confidence: 99%